STUDY OF THE PREVALENCE OF BURNOUT SYNDROME AMONG MUSIC TEACHERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Purpose: To investigate the prevalence of burnout syndrome among music educators by determining the influence of professional experience, job satisfaction, and certain individual-demographic factors. Methods: The study involved 71 music educators from the vocational education system. A direct survey method was used, along with a methodology for investigating burnout syndrome (MBI) and mathematical-statistical methods for data processing with SPSS Statistics 23.0. Differences are considered statistically significant at p≤0.01. Results: According to the level of emotional exhaustion, the majority of teachers (45.1%) fall into the low category. The proportion of those in the moderately expressed category is close (42.3%), while 12.6% report a high level of emotional exhaustion. In terms of depersonalization/dehumanization, the low level is predominant (59.2%), with only 14.1% showing a very high degree of this indicator. Regarding the degree of reduced work capacity/reduced professional achievement, 50.7% fall into the low expressed category, while a relatively high percentage (33.8%) is noted for the moderate expression of the indicator. Significantly pronounced statistically significant relationships were found between the components of emotional exhaustion, reduced work capacity/reduced professional achievement, and job satisfaction. A moderately expressed relationship was found between age and the component of reduced work capacity/reduced professional achievement. Conclusions: In the future, there is a need for more in-depth studies focusing on the personal and environmental factors that influence the formation and development of burnout syndrome in the target group.